Neuroprotection against Amyloid-β-Induced DNA Double-Strand Breaks Is Mediated by Multiple Retinoic Acid-Dependent Pathways. (20th March 2020) - Colas, Julien; Chessel, Natacha; Ouared, Allaeddine; Gruz-Gibelli, Emmanuelle; Marin, Pascale; Herrmann, François R.; Savioz, Armand
Abstract : In this study, we have investigated the role of all- trans -retinoic acid (RA) as a neuroprotective agent against A β 1-42 -induced DNA double-strand breaks (DSBs) in neuronal SH-SY5Y and astrocytic DI TNC1 cell lines and in murine brain tissues, by single-cell gel electrophoresis. We showed that RA does not only repair A β 1-42 -induced DSBs, as already known, but also prevents their occurrence. This effect is independent of that of other antioxidants studied, such as vitamin C, and appears to be mediated, at least in part, by changes in expression, not of the RAR α, but of the PPAR β / δ and of antiamyloidogenic proteins, such as ADAM10, implying a decreased production of endogenous A β . Whereas A β 1-42 needs transcription and translation for DSB production, RA protects against A β 1-42 -induced DSBs at the posttranslational level through both the RAR α / β / γ and PPAR β / δ receptors as demonstrated by using specific antagonists. Furthermore, it could be shown by a proximity ligation assay that the PPAR β / δ -RXR interactions, not the RAR α / β / γ -RXR interactions, increased in the cells when a 10 min RA treatment was followed by a 20 min A β 1-42 treatment. Thus, the PPAR β / δ receptor, known for its antiapoptotic function, might for these short-time treatments play a role in neuroprotection via PPAR β / δ -RXR heterodimerization and possibly expression of antiamyloidogenic genes. Overall, this study shows that RA can not only repair A β 1-42 -induced DSBs but also prevent them via the RAR α / β / γ and PPAR β / δ receptors. It suggests that the RA-dependent pathways belong to an anti-DSB Adaptative Gene Expression (DSB-AGE) system that can be targeted by prevention strategies to preserve memory in Alzheimer's disease and aging.